Construction of pBAD/TOPO® thio fusion-pla2 gene cassette in escherichia coli / Hanis Hanum Zulkifly - Zulkifly, Hanis Hanum (2006)
Aim - To construct pBAD/TOPO® Thio Fusion-p/a1 gene cassette in Escherichia coli Method - The method of this study started of with conformation of the original clone (p/a1) synthesized by First BASE Laboratories followed by the amplification of the gene (pla2) using PCR. Then, the amplified gene was ligated into a vector which is pBAD/TOPO® Thio Fusion. The entire plasmid was then transformed into a bacterial host, £. coli strain TOP I 0. Analysis of positive recombinant was done by restriction digestion. analyzing PCR and DNA sequencing. Prior to performing restriction digestion, PCR and DNA sequencing, the plasmid which carries the gene of interest (GOI) must be extracted from the bacterial host. Extraction was done using commercial DNA extraction kit (Wizard'" Plus Minipreps DNA Purification System, Promega). Conclusion - This study represent the construction of bacterial expression system for heterologous expression of pla, in £. coli. It can be concluded that it is a success to construct pBAD/TOPOl!, Thio Fusion-o/a, plasmid in £. coli. It has been proven that the nucleotide sequence of pla2 gene exhibits high homology to the corresponding region of the porcine PLA2 sequence.